Measures to improve energy efficiency of building utility systems - A. S. Gavrilov; A. E. Sergeev (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The goal of the study is to identify ways to improve energy efficiency by conducting a comprehensive analysis of engineering systems of a house, taking into account the existing model of energy supply and by monitoring the indicators of influence on the efficiency of engineering and technical equipment. Methods. The main method is based on a survey of the level of energy efficiency of heating and hot water supply systems. Results. The article discusses the concept of energy efficiency of a building, energy efficiency class, main utility systems of a residential building, indicators of influence on the state of systems, engineering component and ways to improve it. The article addresses issues related to a full analysis of existing systems in order to assess the implementation of necessary energy-saving measures, as well as their risks and benefits. The possibilities of controlling energy consumption and efficiency of works carried out due to the reconstruction of utility systems of the building have been determined. The results of the analysis of energy-efficient measures, and the feasibility of implementing each of them have been determined in order to identify optimal solutions. Conclusion. Increasing the energy efficiency of building utility systems is one of the priority tasks for creating comfortable living conditions. The energy efficiency class of building utility systems is established according to the state of a system, takes into account all quality indicators for energy consumption, and the energy certificate fully shows the level of energy efficiency.